Implications of Identifying Additional Cerebral Metastases during Gamma Knife Radiosurgery. (15th August 2011) - Patel, Toral R.; Ozturk, Ali K.; Knisely, Jonathan P. S.; Chiang, Veronica L.
Abstract : Introduction . Gamma Knife radiosurgery (GK-SRS) is commonly used to treat cerebral metastases. Although additional intracranial metastases are often found on the day of GK-SRS, the significance of finding them is unknown. Methods . A retrospective review of 133 patients undergoing GK-SRS for cerebral metastases was performed. The change in number of metastases detected between initial referral magnetic resonance imaging (MRI) and subsequent treatment MRI was quantified. Multivariate and Kaplan-Meier analyses were employed to examine the significance of identifying additional lesions. Results . Additional lesions were identified in 41% of patients. An increasing number of metastases on referral MRI (P = 0.001 ) and the presence of progressive systemic disease (P = 0.003 ) were predictive of identifying additional metastases. Median survival was 6.9 months for patients with additional metastases, compared to 12.1 months for patients without additional metastases (hazard ratio 1.56, P = 0.021 ). Conclusions . Identifying additional metastases on the day of GK-SRS may add important prognostic information.